In-situ investigate on the microstructure evolution, deformation and fracture mechanism of Mg-Gd-Zn-Mn alloy with varies of LPSO volume fraction - Shiyu Luan; Lei Zhang; Lijia Chen; Jinhui Wang; Peipeng Jin (Journal of Materials Research and Technology, 2023)
The induction of long-period stacking ordered (LPSO) phase through heat treatment was an effective method to strengthen magnesium alloys. In this study, the volume fraction of lamellar LPSO in the Mg-4Gd-1Zn-0.5Mn alloy was controlled by optimizing the heat treatment process. The research findings showed that with increasing heat treatment time, the volume fraction of LPSO initially increased then decreased until disappearing. The alloy treated at 500 °C for 2 h exhibited the highest volume fraction of lamellar LPSO, increasing from 1.64% to 13.68%. Further in-situ tensile tests were conducted on two types of alloys contain higher LPSO fraction (HL) and lower LPSO fraction (LL) at ambient temperature. The increased critical shear stress (CRSS) and obstacle effects on dislocations caused by LPSO effectively enhanced the strength of the alloy. The dominant deformation mechanisms of both HL and LL alloys are basal slip and twinning during tensile deformation. However, the HL alloy activated more non-basal slip significantly, which was ascribed to the activation of non-basal slip by LPSO kinking during deformation. Additionally, the bending and kinking of LPSO effectively restricted crack initiation and propagation, thereby enhancing the plasticity. The HL alloy exhibited fewer twin boundaries after deformation, which was attributed to the hindrance of twinning extension by LPSO.